2016
DOI: 10.7150/ijms.14877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HMGB1 Polymorphisms on the Susceptibility and Progression of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a malignancy of liver and a leading cause of cancer mortality worldwide. Its management is compounded by biological and clinical heterogeneity. These interindividual genetic variations can modulate the effects of HCC treatment. High-mobility group box protein 1 (HMGB1) is a well investigated, ubiquitous nuclear protein found in eukaryotic cells that plays a multiple biological roles such as DNA stability, program cell death, immune response, and furthermore in cancer progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…So far the physiological significance of rs1045411 is uncertain, and the location of this polymorphism could suggest a role in mRNA stability as microRNAs can bind the 3'-untranslated regions of mRNA transcripts and inhibit gene expression at the posttranscriptional level. Moreover, in the present study, the mutant allele of rs1045411 was associated with a significantly increased risk of hepatocellualr carcinoma, while another study in a Taiwan population found that carriers of this mutant allele had a lower risk [ 25 ], likely due to differences in lifestyles, diets or study power. On the other hand, the polymorphism rs2070600 is non-synonymous (Gly82Ser) in the exon 3 of RAGE gene, and the association of this polymorphism was significant with a wide range of cancer types, including lung cancer [ 26 ], breast cancer [ 27 ], ovarian cancer [ 28 ] and colorectal cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 52%
“…So far the physiological significance of rs1045411 is uncertain, and the location of this polymorphism could suggest a role in mRNA stability as microRNAs can bind the 3'-untranslated regions of mRNA transcripts and inhibit gene expression at the posttranscriptional level. Moreover, in the present study, the mutant allele of rs1045411 was associated with a significantly increased risk of hepatocellualr carcinoma, while another study in a Taiwan population found that carriers of this mutant allele had a lower risk [ 25 ], likely due to differences in lifestyles, diets or study power. On the other hand, the polymorphism rs2070600 is non-synonymous (Gly82Ser) in the exon 3 of RAGE gene, and the association of this polymorphism was significant with a wide range of cancer types, including lung cancer [ 26 ], breast cancer [ 27 ], ovarian cancer [ 28 ] and colorectal cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 52%
“…Wang et al [30] indicated that HCC patients carrying at least one C allele at rs1412125 showed a low risk of distant metastasis. Supic et al [29] revealed that rs2249825 and rs3742305 polymorphisms might be associated with OSCC survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests an association between SNPs in certain genes and HCC susceptibility[81]. GWAS have emerged as a new approach for identifying less penetrant cancer susceptibility alleles that might be associated with the initiation and progression of cancer.…”
Section: Snpsmentioning
confidence: 99%